Dental health of patients with X-linked hypophosphatemia: A controlled study - Larsson, Amila; Regnstrand, Tobias; Skott, Pia; Mäkitie, Outi; Björnsdottir, Sigridur; Garming-Legert, Karin (Frontiers in Oral Health, 2023)
Objective The present study compared the dental health of patients with X-linked hypophosphatemia (XLH) with healthy age- and gender-matched controls to increase our knowledge of the impact of XLH on oral health. Materials and methods Twenty-two adult patients with XLH in the Stockholm region of Sweden were referred to the Department of Orofacial Medicine at Karolinska Institutet for an extended clinical and radiological examination. Pre-existing radiologic examinations of 44 healthy age- and gender-matched controls were retrieved from the Department of Oral Radiology, at Karolinska Institutet. Results The 22 patients with XLH (15 females, median age 38 years, range 20–71; 7 males, median age 49 years, range 24–67) had a significantly higher number of root-filled teeth compared to healthy controls (p = .001). In the XLH group, females had significantly better oral health than males, especially concerning endodontic and cariological status (p's = .01 and .02, respectively). Periodontal status differed non-significantly between the XLH and control groups. Conclusion Patients with XLH had a significantly lower oral health status compared to a healthy population especially concerning endodontic conditions. Male patients with XLH had a higher risk of poor oral health compared to female patients with XLH.